1996
DOI: 10.1046/j.1365-2567.1996.d01-707.x
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte–macropha ge colony‐stimulating factor down‐regulates CD14 expression on monocytes

Abstract: SUMMARYCD14 is a differentiation-stage-linked glycosyl-phophatidyl-inositol-linked glycoprotein on human peripheral blood monocytes and tissue macrophages, which functions as a receptor for lipopolysaccharide. Here, the effects of granulocyte-macrophage colony-stimulating factor (GM-CSF), a cytokine with proliferation-and differentiation-inducing properties on myeloid lineage cells, were studied on CD14 expression by peripheral blood cells. GM-CSF down-regulated the membrane expression of CD14 on monocytes, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 41 publications
3
32
1
Order By: Relevance
“…Survival rates of differentiated macrophages varied in the following order: GM-CSF Ͼ M-CSF Ͼ hAB (from 80 to 50%, respectively). Cell surface marker analysis on day 4 macrophages showed a decrease in CD14 surface labeling in macrophages differentiated in GM-CSF, as compared to the starting monocyte population and to macrophages differentiated under the remaining conditions, as reported previously (Table 1) (16,17). Macrophages differentiated under the three conditions, however, had similar functional properties (as determined by phagocytosis and mixed lymphocyte reaction; data not shown).…”
Section: Fig 5 Comparison Between Moloney MLV Andsupporting
confidence: 85%
“…Survival rates of differentiated macrophages varied in the following order: GM-CSF Ͼ M-CSF Ͼ hAB (from 80 to 50%, respectively). Cell surface marker analysis on day 4 macrophages showed a decrease in CD14 surface labeling in macrophages differentiated in GM-CSF, as compared to the starting monocyte population and to macrophages differentiated under the remaining conditions, as reported previously (Table 1) (16,17). Macrophages differentiated under the three conditions, however, had similar functional properties (as determined by phagocytosis and mixed lymphocyte reaction; data not shown).…”
Section: Fig 5 Comparison Between Moloney MLV Andsupporting
confidence: 85%
“…As 2 O 3 also decreased expression of CD71, a well-known macrophagic differentiation marker (18). In contrast, it markedly increased that of CD14, a typical marker of human blood monocytes, down-regulated by GM-CSF during macrophagic differentiation (26). However, a concentration of 1 M As 2 O 3 failed to modify CD11c levels, which indicates that metalloid effects were not due to a general alteration of surface markers.…”
Section: As 2 O 3 Alters Phenotype Of Human Macrophagesmentioning
confidence: 86%
“…We and others have shown that neonatal monocytes are phenotypically less mature than adult monocytes (28). Down-regulation of CD14 expression might represent a rapid adaptation of the host to stress (11). Hence, slower downregulation of CD14 expression in cord blood implies that the ability of adaptation to stress of CBMC is less than that of adult monocytes when challenged.…”
Section: Cd4mentioning
confidence: 86%
“…GM-CSF is a well-known stimulus for the activation, differentiation, and survival of monocytes. GM-CSF can reduce the CD14 expression of PBMC after 3 d of culture (11). When monocytes were cultured for 7 d with GM-CSF and serum, CD14 was, however, up-regulated, leading to a higher sensitivity toward LPS stimulation (31).…”
Section: Cd4mentioning
confidence: 98%